Another Case of De Novo 3q26.33q27.3 Microdeletion and Its Medicolegal Sequel - Ugo Indraccolo; Salvatore Renato Indraccolo; Piergiorgio Fedeli (Case Reports in Obstetrics and Gynecology)
A new case of a de novo 3q26.33q27.3 microdeletion is reported. The fetus had a sonographically undiagnosable polymalformative syndrome. The case highlights the difficulties of echographic diagnosis of such syndromes and leads to reflection on the difficulties of appropriate counselling in cases of uncertainty.